Formation, Maintenance and Success of Strategic Alliances in a Manufacturing Supply Chain - Loke, Siew Phaik (2008)
Current attempts to study strategic alliances have been hampered by the lack of a unified theory. In this dissertation, resource-based theory, knowledge-based view, contingency theory, transaction cost theory, social exchange theory, and personal relationship theory have been integrated to examine factors relating to strategic alliances in manufacturing supply chains. The factors used in this research: strategic alliance motives, environment, asset specificity, perception of opportunistic behavior, degree of interdependence, degree of integration, and strategic alliance outcomes. Interviews and survey procedures have been used to sample senior executives involved with manufacturing operations and supply chain management. Path analysis using LISREL has been employed to test the integrated research model. Results indicate that strategic alliance formation is influenced by motives and environment. Strategic alliance motives have a positive impact on task, goal and reward interdependence, as well as on the degree of integration (communication, trust and commitment) between strategic alliance partners. Investment in specific assets reduces levels of perceived opportunism and increased levels of interdependence and integration. Perception of opportunistic behavior negatively influences interdependence and integration. Interdependence has been found to have a strong positive effect on integration. Strategic alliance success is determined by goal achievement, value creation and satisfaction. Environment does not moderate the effect of strategic alliance motives on integration. These findings offer a better understanding of inter-firm collaboration and may be valuable in preparing managers for the challenges of strategic alliance management.